The Development And Validation Of A Framework For Teaching Competencies In Pedagogy Content Knowledge And Instructional Quality - Sedek, Muliati; Syed Hassan, Syed Najmuddin; Robani, Anidah; Kamaruddin, Mohd Fauzi (Medwell Journals, 2014)
-